2022
DOI: 10.1590/s2175-97902022e191055
|View full text |Cite
|
Sign up to set email alerts
|

Development of fluorescent- and radio-traceable T1307-polymeric micelles as biomedical agents for cancer diagnosis: biodistribution on 4T1 tumor-bearing mice

Abstract: In recent years, nanocarriers have been studied as promising pharmaceutical tools for controlled drug-delivery, treatment-efficacy follow-up and disease imaging. Among them, X-shaped amphiphilic polymeric micelles (Tetronic®, poloxamines) display great potential due to their biocompatibility and non-toxic effects, among others. In the present work, polymeric micelles based on the T1307 copolymer were initially decorated with a 4,4-difluoro-4-bora-3a,4a-diazas-indacene (BODIPY)-fluorophore in order to determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Similarly, Puig-Rigall et al 34 developed formulations of miltefosine (MF), an alkylphospholipid for breast cancer treatment, using TPGS, T1107 and T904 and noted improved activity of MF with T904 against intracellular amastigotes. Lecot et al 35 in a recent study used T1307 modified with a 4,4-difluoro-4-bora-3a,4a-diaza- s -indacene fluorophore for assessing it's in vivo biodistribution on 4T1 tumor-bearing mice and attained results revealing promising role of T1307 micelles as radio tracer agents for breast cancer imaging. Castelli et al 36 observed the co-association of aptamer Sgc8-c-Alexa647, a biomarker in cancer with different nanostructures like F127, T1307 and pegylated liposomes.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Puig-Rigall et al 34 developed formulations of miltefosine (MF), an alkylphospholipid for breast cancer treatment, using TPGS, T1107 and T904 and noted improved activity of MF with T904 against intracellular amastigotes. Lecot et al 35 in a recent study used T1307 modified with a 4,4-difluoro-4-bora-3a,4a-diaza- s -indacene fluorophore for assessing it's in vivo biodistribution on 4T1 tumor-bearing mice and attained results revealing promising role of T1307 micelles as radio tracer agents for breast cancer imaging. Castelli et al 36 observed the co-association of aptamer Sgc8-c-Alexa647, a biomarker in cancer with different nanostructures like F127, T1307 and pegylated liposomes.…”
Section: Introductionmentioning
confidence: 99%